2012
DOI: 10.1097/iae.0b013e31821e1f7c
|View full text |Cite
|
Sign up to set email alerts
|

Further Characterization of Ocular Safety Profile of Commercially Available Preserved and Preservative-Free Triamcinolone Acetonide

Abstract: The equivalent triamcinolone acetonide doses to 0.1 mL (4 or 12 mg) intravitreal injection for human eye were found safe in guinea pig eyes. No significant difference was noted for 0.1 mL intravitreal injection between Kenalog-40 and Triesence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 33 publications
1
4
0
1
Order By: Relevance
“…However, pilot studies of intravitreal/subconjunctival injection of the commercial TA suspension (Transton®) have shown incidents of high intraocular pressure and cataracts. [35][36][37] In our results, we also observed that four of the eleven rats (∼36%) administrated with the TA suspension exhibited the high IOP after 5 days of injection and two of the eleven (∼18%) rats administrated with the 2.0 wt% TA suspension had cataracts. Interestingly, no such complications were observed after the administration of our TA hydrogel during the whole period of study.…”
Section: In Vivo Compatibility Testsupporting
confidence: 72%
“…However, pilot studies of intravitreal/subconjunctival injection of the commercial TA suspension (Transton®) have shown incidents of high intraocular pressure and cataracts. [35][36][37] In our results, we also observed that four of the eleven rats (∼36%) administrated with the TA suspension exhibited the high IOP after 5 days of injection and two of the eleven (∼18%) rats administrated with the 2.0 wt% TA suspension had cataracts. Interestingly, no such complications were observed after the administration of our TA hydrogel during the whole period of study.…”
Section: In Vivo Compatibility Testsupporting
confidence: 72%
“…For suprachoroidal TA injection, only one eye of each animal was used and the fellow eye was left untouched for control purpose. Following suprachoroidal injection, the eyes were monitored by ocular tomometry, indirect ophthalmoscopy, fundus photography, electroretinography (ERG), and histology after sacrifice as previously reported [24].…”
Section: Safety Studymentioning
confidence: 99%
“…Preservative-free TA formulations have been developed and registered as medical devices for intended intravitreal use; however, controversial results have been obtained with regard to their safety profiles. 9 , 15 17 …”
Section: Introductionmentioning
confidence: 99%